DC voltage control strategy of chain star STATCOM with second‐order harmonic suppression. Issue 14 (1st November 2016) - Wang, Yingjie; Chai, Yushuo; Tang, Jianbo; Yuan, Xibo; Xia, Chenyang
Abstract : Chain static synchronous compensators (STATCOMs) with star structure produce second‐order harmonic fluctuations on the DC side. This effect is often ignored and only the average voltage value is taken into consideration when describing this system for control purpose. In this study, the unbalance of per‐phase DC voltages caused by active power absorbed and consumed by the chain is analysed. The steady‐state expressions regarding the average capacitor voltage balancing between phase clusters as well as the suppression of second‐order harmonic fluctuation are obtained, respectively, based on the injection of fundamental and third‐order harmonic zero‐sequence voltages. Although the expressions are helpful to understand the essence of DC capacitor voltage control, this method has complicated calculation process and the calculation results may be beyond the modulation limit. Therefore, it is not conducive in real‐time control. For this reason, a new control strategy based on the instantaneous zero‐sequence voltage injection is proposed. The evaluation function with the transient variables is established to get the instantaneous value of the zero‐sequence voltage including fundamental and third‐order harmonic components. The fundamental and third‐order harmonic zero‐sequence voltages are automatically allocated to fully use the remaining modulation capacity. Finally, simulation and experimental results are provided, which verifies the correctness of the theoretical analysis and the high performance of the proposed method.